Psoriatic Arthritis Is an Indicator of Significant Renal Damage in Patients with Psoriasis: An Observational and Epidemiological Study - Abidullah Khan; Iqbal Haider; Maimoona Ayub; Mohammad Humayun (International Journal of Inflammation)
Background. Psoriasis affects joints in around 30% of the patients. Recent studies have demonstrated an increased risk of essential hypertension, ischemic heart disease, and stroke in psoriatic patients. However, the prevalence of renal disease in patients with psoriasis has not been evaluated properly. Objectives. Objectives were to evaluate renal functions in patients with psoriasis and to assess any possible relationship of renal failure with psoriasis and psoriatic arthritis. Methods. In this cross-sectional study, 30 participants were recruited into the following three groups: group-A, psoriatic arthritis; group-B, psoriasis without arthritis; and group-C, healthy subjects. Renal function tests were performed for every participant of each group. The data was analyzed by using SPSS version 16. Chi-squared and one-way ANOVA tests were applied, considering a P value of less than 0.05 as a standard criterion. Results. Serum creatinine, urea, and phosphate were the highest in group-A, higher in group-B, and normal in group-C, P<0.05. Similarly, GFR was the lowest in group-A, lower in group-B, and normal in group-C. The difference in mean GFR values was statistically significant, F(2)=355, P<0.001. Moreover, proteinuria (gm/day) was seen in 96.7% of the patients with psoriatic arthritis, (M=1.18±0.55, P<0.05) against 10% of the psoriatic patients without arthritis (M=0.41±0.10, P<0.05). Conclusion. Derangement of renal function is more prevalent in psoriatic patients, especially in those with concomitant psoriatic arthritis. Therefore, each psoriatic patient must be routinely screened for an underlying renal failure.